Mechanical Strain Alters Cellular and Nuclear Dynamics at Early Stages of Oligodendrocyte Differentiation - Makhija, Ekta; Jagielska, Anna; Zhu, Lena; Bost, Alexander C.; Ong, William; Chew, Sing Y.; Shivashankar, G. V.; Van Vliet, Krystyn J. (Frontiers in Cellular Neuroscience, 2018)
Mechanical and physical stimuli including material stiffness and topography or applied mechanical strain have been demonstrated to modulate differentiation of glial progenitor and neural stem cells. Recent studies probing such mechanotransduction in oligodendrocytes have focused chiefly on the biomolecular components. However, the cell-level biophysical changes associated with such responses remain largely unknown. Here, we explored mechanotransduction in oligodendrocyte progenitor cells (OPCs) during the first 48 h of differentiation induction by quantifying the biophysical state in terms of nuclear dynamics, cytoskeleton organization, and cell migration. We compared these mechanophenotypic changes in OPCs exposed to both chemical cues (differentiation factors) and mechanical cues (static tensile strain of 10%) with those exposed to only those chemical cues. We observed that mechanical strain significantly hastened the dampening of nuclear fluctuations and decreased OPC migration, consistent with the progression of differentiation. Those biophysical changes were accompanied by increased production of the intracellular microtubule network. These observations provide insights into mechanisms by which mechanical strain of physiological magnitude could promote differentiation of progenitor cells to oligodendrocytes via inducing intracellular biophysical responses over hours to days post induction.